Demographics, Awareness and Pattern of Diabetic Retinopathy among Diabetic Patients - Anjila Basnet; Raghunandan Byanju; Samir Thapa; Sanjit Kumar Shah; Suman Simkhada (Journal of Nobel Medical College)
Background: Diabetic retinopathy is one of the emerging causes of blindness in developing countries. This study was carried out among diabetic patients to determine the demographics, severity of diabetic retinopathy and also to assess the level of awareness of diabetic eye disease.